2004
DOI: 10.1023/b:jadd.0000018072.42845.83
|View full text |Cite
|
Sign up to set email alerts
|

Matching Procedures in Autism Research: Evidence from Meta-Analytic Studies

Abstract: In this paper, we summarize some of our findings from a series of three meta-analyses and discuss their implications for autism research. In the first meta-analysis, we examined studies addressing the theory of mind hypothesis in autism. This analysis revealed that theory of mind disabilities are not unique to autism, although what may be unique is the severity of the dysfunction in this group. Variables such as the chronological and mental age of the participants, and the matching procedures that the research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 22 publications
1
26
0
2
Order By: Relevance
“…Although the PPVTappears to be a good choice for the current study (because receptive word learning is of interest), concerns regarding picture vocabulary tests for AD children have been raised. Most worrisome is that such tests tend to overestimate the language abilities of AD children because many are adept at labeling objects (Shaked & Yirmiya, 2004). Thus, the receptive language of TD children may be more advanced than AD children despite comparable PPVT scores.…”
Section: Dasmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the PPVTappears to be a good choice for the current study (because receptive word learning is of interest), concerns regarding picture vocabulary tests for AD children have been raised. Most worrisome is that such tests tend to overestimate the language abilities of AD children because many are adept at labeling objects (Shaked & Yirmiya, 2004). Thus, the receptive language of TD children may be more advanced than AD children despite comparable PPVT scores.…”
Section: Dasmentioning
confidence: 99%
“…It has been suggested that future studies should use matched children with a specific language delay (Tager-Flusberg, 2004; but see Burack et al, 2004;Charman, 2004). Furthermore, our LA group was assembled using PPVT scores, a matching method that has been called into question for overestimating the verbal abilities of AD children (Shaked & Yirmiya, 2004).…”
Section: Implications For Word Learningmentioning
confidence: 99%
“…Le résultat intéressant de l'analyse confirme que cette difficulté n'est pourtant pas spécifique à l'autisme. En effet, les enfants avec déficience intellectuelle rencontrent également de grandes difficultés à attribuer des états mentaux et, au vu des problèmes d'appariement pour constituer des groupes contrôles auxquels comparer les enfants avec autisme [14], il est légitime de se poser la ques tion de la spécificité de ce symptôme.…”
Section: La Cognition Socialeunclassified
“…Sullivan and TagerFlusberg 1999) putatively constitutes a methodological limitation (e.g. Shaked and Yirmiya 2004), which may have contributed to previous contradictory findings. Here we hypothesized that if the WS uneven cognitive profile impacts on TOM ability in this disorder, this should be evidenced by increased performance on verbal relative to visual TOM tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Note that CA and MA selection criteria were not restricted because previous studies suggest that imposing such restrictions may substantially influence results on TOM measures (e.g. Shaked and Yirmiya 2004). Full-scale IQ scores ranged from 40 to 81 (M = 57.5; SD = 11.0), with verbal IQ (VIQ) scores ranging from 46 to 91 (M = 65.5; SD = 14.3) and performance IQ (PIQ) scores ranging from 46 to 80 (M = 55.4; SD = 9.0).…”
Section: Introductionmentioning
confidence: 99%